Formation of MoOx barrier layer under atmospheric based condition to control MoSe2 formation in CIGS thin film solar cell - Ong K.H.; Ramasamy A.; Arnou P.; Maniscalco B.; W. Bowers J.; Chandan Kumar C.; Bte Marsadek M. (Taylor and Francis Ltd., 2023)
Copper compounds; Efficiency; Gallium compounds; Layered semiconductors; Molybdenum oxide; Plasma jets; Solar cells; Thin film solar cells; Thin films; Atmospheric plasmas; Barrier layers; CIGS thin films; Gallium selenides; MoSe2; Selenium compounds